KANDUNGAN VITAMIN C PADA OVARIUM IKAN LELE (Clarias gariepinus) SAAT SIKLUS REPRODUKSI - Sinjal, Hengky J (JURNAL PERIKANAN DAN KELAUTAN TROPIS, 2010)
Vitamin C content in the ovarium of African Catfish (Clarias gariepinus) during reproductive cycle was investigated. One hundred twenty samples of females covering different stages of reproductive cycle were collected from fresh water ponds. The fishes were sacrifized and the ovarium were collected for analysis of gonad maturation stage (TKG), oocyt structure and vitamin C content in the ovarium. Â Results indicated that average of vitamin C content of ovarium at stage I was 74.33mg/g (wet weight). The maximum content was found in stage III at level of 155.98mg/g (wet weight) and afterwards in the next stage vitamin C content decreased. The maximum of oocyt stadium 3 (oocyt vitelogenesis) was also found at this stage III. The findings indicate that vitamin C has a role in the reproductive cycle of catfish and its content is related to ovarium development and oogenesis.